Energy Efficiency Use of Amount of Light in a Room Based on Number of People Using IoT and Image Processing - Latansyah Maulana Virnandani; Azam Muzakhim Imammuddin; Mochammad Junus (Politeknik Negeri Malang, 2022)
A room with too humid conditions can cause mold and bacteria to multiply quickly. The humidity level of the room can be influenced by several factors such as the temperature level and the intensity of light entering the room. Even so, the use of lighting as a sterilizer is currently still lacking in reducing the level of humidity in the room. For this reason, it is necessary to develop technology in the form of a control system for the use of led and ultraviolet lamps in the study room by utilizing the IoT system, so that it can turn on the lights and utilize electrical energy. In this study, the Internet of Things system was applied as a control for Web cameras, Gyml 8511, DHT11, and BH1750 sensors. Data from the sensor will be sent from Arduino uno to a local server, namely raspberry pi 4 using NRF24L01. The communication system between nodes is designed with a mesh topology that can determine the fastest route in the process of sending information. The result of this research is monitoring on the web display that displays the condition of the class and the condition of the lights. From the experimental results, it is found that the mesh communication system can work well.